1996
DOI: 10.1021/jp951561t
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Hydrogen Bonding in Supercritical Water

Abstract: The effect of temperature on hydrogen bonding in supercritical water is investigated at densities of 257 and 659 kg/m3 and at temperatures in the range 773−1073 K using molecular dynamics simulations with a flexible simple point charge water potential. An energetic criterion is used to distinguish hydrogen-bonded pairs from non-hydrogen-bonded pairs. The number of hydrogen bonds per water molecule decreases as the temperature is increased. Hydrogen-bonded clusters in supercritical water consist of fewer than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(97 citation statements)
references
References 25 publications
5
88
0
4
Order By: Relevance
“…Similar hydrogen bonding structure and the hydration of Cl -in hydrothermal NaCl solutions were also quantitatively addressed by experimental (IR and Raman) and computational (classical MD) approaches [35]. They found that the feature of the NaCl structure has a considerable as observed by previous studies for H-bonds (the lifetime of H-bonds in supercritical water is 0.2-0.5 ps [36,37]; see reviews by [38]). The total number of H-bonds increases as a function of density, consistent with the trends observed in Figures 4(a) and 5(a).…”
Section: Hydrogenmentioning
confidence: 56%
“…Similar hydrogen bonding structure and the hydration of Cl -in hydrothermal NaCl solutions were also quantitatively addressed by experimental (IR and Raman) and computational (classical MD) approaches [35]. They found that the feature of the NaCl structure has a considerable as observed by previous studies for H-bonds (the lifetime of H-bonds in supercritical water is 0.2-0.5 ps [36,37]; see reviews by [38]). The total number of H-bonds increases as a function of density, consistent with the trends observed in Figures 4(a) and 5(a).…”
Section: Hydrogenmentioning
confidence: 56%
“…Nevertheless, calculation of a basic dynamic characteristic of hydrogen bonding, namely average HB lifetime, was performed by several authors only. In the studies [20,21], calculations were made for a few series of T, P, and q, but these disembodied results did not allow to make up a general picture of average HB lifetime as a function of state parameters. Thus, we found appropriate to perform comprehensive study of HB lifetime dependence on temperature and density in a wide region on state diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Structural properties of SCW have been extensively studied using different experimental procedures [3][4][5][6][7][8][9] as well as computer simulation with different molecular models. [10][11][12][13][14][15][16][17][18] A central aspect in this discussion is the change in the hydrogen bond network compared to the situation in normal water. There is a reduction in the number of hydrogen bonds 8 and the tetrahedral ordering of the water molecules, a characteristic of the ambient conditions, is missing in the supercritical regime where the density is decreased.…”
Section: Introductionmentioning
confidence: 99%